CONCEPTS OF QUALITY MANAGEMENT OF EDUCATION: FROM HISTORY TO PRESENT - Chernenko, Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2023)
Introduction. Quality management of education is an important direction of reforming and developing the education system in Ukraine, bringing it up to EU standards. It is worth noting that the concept of quality management of education has deep historical roots and has gone a long way in its development.